Promoting effect of H2O over macroporous Ce-Zr catalysts in soot oxidation - Park, Chung Sun; Lee, Mill Woo; Lee, Jae Hwan; Jeong, Eun Jin; Lee, Seong Ho; Choung, Jin Woo; Kim, Chang Hwan; Ham, Hyung Chul; Lee, Kwan-Young (ELSEVIER, 2019)
Gasoline particulate filters (GPFs) contain small amounts of O-2 and excess H2O; however, the effect of H2O on soot oxidation has not been thoroughly explored to date. Thus, it is necessary to understand the effect of H2O on soot oxidation to improve the catalytic performance in GPFs. This study investigates the role of H2O in soot oxidation on macroporous Ce-Zr mixed oxide catalysts (M-CeZr). The results revealed an improvement in the catalytic activity of soot oxidation in the presence of H2O over that afforded under oxygen-only conditions. Since the mechanism of soot oxidation under dry conditions involves the conversion of gaseous oxygen to active oxygen (O-x(-)) species on the oxygen vacancies of the catalyst, O-x(-) and oxygen vacancy are critical factors that affect the catalytic performance in the absence of H2O. Notably, when H2O was introduced into the reaction, it was predominantly used as an oxidant rather than gaseous oxygen. Further, the dissociation of H2O into active oxygen over the catalyst surface was not related to the number of oxygen vacancies. Therefore, even when the catalyst comprised few oxygen vacancies, its activity improved under wet conditions. In addition, although the catalysts were damaged by high temperatures, the catalytic performance was maintained in the presence of H2O, unless the morphology of the catalysts collapsed.